Composting of Turkey Brooder Litter in South Carolina: An On-Farm Demonstration Project - Chastin, John P.; Rollins, P. Andrew; Kathy P. Moore (Journal of Agricultural Systems, Technology, and Management, 2013)
A composting demonstration project was conducted on a turkey brooder farm in one of the major turkey production areas of South Carolina. Litter was removed from the barns and was moved to a composting shed located on the farm. Data were collected to determine the content of plant nutrients, carbon, TS, VS, FS, and C:N in the litter before and after composting. Windrow temperatures were monitored to determine if the required temperature conditions were obtained for pathogen treatment. Turkey brooder litter composted well as indicated by an average windrow temperature of 59°C for 59 days. The final product was very stable as indicated by a very low CO2 evolution rate (0.2 mg CO2-C/g organic matter/day). The C:N of the brooder litter was 22 and the C:N of the compost product was 23. It was determined that N losses during composting (53%) caused the C:N to remain constant. Therefore, reduction in C:N was not found to be a good indicator of compost stability in this field study. Comparison of the composition of brooder litter with turkey grow-out litter indicated that brooder litter contained 29% less plant available nitrogen, and cost 47% more to spread on distant fields. As a result, composting may be a more desirable management option in such cases.